2011
DOI: 10.1007/s10562-011-0688-x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Cinnamaldehyde on Pt and Pt-Fe Catalysts Supported on Zeolite P

Abstract: Pt-and Pt-Fe based catalysts on zeolite P (ZP) support have been prepared and widely characterized by surface area and porosity, XRD, SEM, TEM, TPR, in order to investigate their morphological and microstructural properties. The catalysts have been tested in the selective liquid-phase hydrogenation of cinnamaldehyde. Kinetic tests have shown the beneficial effect of Fe promoter on the catalysts behaviour towards the selective formation of cinnamyl alcohol (85% selectivity to 90% conversion). The ZP supported c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…(b) Bimetallic effect on the activity and selectivity ((▲) CAL and (■)) CRAL). Data have been obtained from refs , , , , , , , and.…”
Section: Selective Hydrogenation Of Ual To Uolmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Bimetallic effect on the activity and selectivity ((▲) CAL and (■)) CRAL). Data have been obtained from refs , , , , , , , and.…”
Section: Selective Hydrogenation Of Ual To Uolmentioning
confidence: 99%
“…10 Yang et al 165 prepared CoIn 3 and CoGa 3 intermetallic compounds from LDH precursors and the electropositive (Ga or In) active sites facilitated the activation of CO. The metal molar ratio showed a significant effect on the bimetallic catalysts and was optimized over the PtCo, 163 PtFe, 107,164 and AuAg 18 catalysts. A small addition of a second metal would effectively increase the selectivity and activity, while a negative effect occurred with further increases of a second metal.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…Moreover, new types of carbon‐based porous materials supported platinum‐based catalysts have a higher selectivity to cinnamyl alcohol, up to 91.1 %, such as carbonized aerosols (S col = 53 %), CNTs (S col = 64 %), graphite (S col = 72 %), rice husk mesoporous carbon (S col = 88 %), graphene oxide (S col = 88 %), and three‐dimensional layered porous carbon (S col = 91.1 %) . On the other hand, platinum‐based catalysts doped with other metals, such as Fe (S col = 85 %, 90 %), Fe 3 O 4 (S col = 94.9 %), Sn (S col = 78 %), and Co (S col = 87.9 %), can also significantly improve the selectivity to cinnamyl alcohol, however, Ni (S col = 8 %, 27.4 %) is an exception.…”
Section: Introductionmentioning
confidence: 99%
“…[6] For this purpose, different approaches have been reported with the aim to increase the conversion and selectivity towards a specific product, which significantly varies with the reaction conditions, solvent, support, catalyst preparation methods, as well as the nature of the metallic phase used. [7][8][9] It has been reported that the use of metals such as Pd, Rh, Cu, Mo usually promote the selective hydrogenation of the C═C double bond, whereas Pt, Ir, Ru, Co and some bimetallic catalysts are more selective towards the hydrogenation of the C═O double bond conjugated in these kind of a,b-unsaturated aldehydes and ketones. [5,[10][11][12] Furthermore, different supports have been used for the selective hydrogenation of cinnamaldehyde, among them: Al 2 O 3 , Zeolites, Nb 2 O 5 , CeO 2 , SiO 2 , TiO 2 , graphite, mesoporous materials, layered double hydroxides, etc.…”
Section: Introductionmentioning
confidence: 99%